2015
DOI: 10.3329/bjas.v44i2.26006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth traits of Aceh cattle at the breeding station in Indrapuri District of Indonesia

Abstract: The present study was conducted using records on four breeding bulls maintained at the Indrapuri's Breeding and Forages Center (IBFC) of Aceh Cattle, Indrapuri district, Indonesia and 52 of their progeny born from 2010 to 2014 through natural mating. Family selection was practiced in this breeding station.Traits included in this study were birth weight at 0 day (BWc), weaning weight at 205 days of age (WWc), yearling weight at 365 days of age (YWc) and final weight at 550 days of age (FWc) Research showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Therefore, low RA value in a bull indicates that selection in this bull is not accurate because of less number of progeny for analysis. (Putra et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, low RA value in a bull indicates that selection in this bull is not accurate because of less number of progeny for analysis. (Putra et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, two records data of birth weight and calving interval were used to select Bali cattle in West Nusa Tenggara (WNT) province. Previous studies reported that BW of calves can be used as the selection criteria to select the best cattle (Bakir et al, 2004;Putra et al, 2015;Said et al, 2016). Moreover, the genetic correlation (rg) between birth and weaning weights in cattle were included of moderate to high categories (rg > 0.50) such as Brangus (0.78), Fogera (0.60) and 0.87 for Sumba Ongole (Neser et al, 2012;Bekele et al, 2016;Putra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%